2014
DOI: 10.4103/0974-8520.159044
|View full text |Cite
|
Sign up to set email alerts
|

Management of spastic cerebral palsy through multiple Ayurveda treatment modalities

Abstract: Background:Cerebral palsy (CP) is a leading cause of childhood disability affecting function and development. The global incidence of CP is 2:1000. It has been reported that children with CP and their caretaker have impaired health-related quality of life (QOL). Of the many types and subtypes of CP, none has any known cure. For a detailed description of the disease CP, though, there is no one to one correlation in Ayurvedic classics; it can be taken as Vata Vyadhi as far as its etiology and symptomatology are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Clinical trials have shown that Cerebral palsy is most effectively treated in the line of management of treatment of diseases caused due to vata (vatavyadhi chikitsa). 11 Vata has been explained to be vitiated by trauma (abhighata) and also injury to vital organs (marmabhighata). 12 Cerebral palsy is also caused by damage pertained to the brain and its cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that Cerebral palsy is most effectively treated in the line of management of treatment of diseases caused due to vata (vatavyadhi chikitsa). 11 Vata has been explained to be vitiated by trauma (abhighata) and also injury to vital organs (marmabhighata). 12 Cerebral palsy is also caused by damage pertained to the brain and its cells.…”
Section: Discussionmentioning
confidence: 99%
“…When vata comes to normalcy development of milestones will become normal. 2 Abhyanga reduces increased muscle tone, improves muscle bulk and power in CP cases. 3 Abhyanga involves cutaneous manipulation and it is considered as one of the prime procedures for mitigating vata.…”
Section: Sarvaanga Abhyangamentioning
confidence: 99%
“…Various panchakarma procedures like Udwartana (medicated powder massage), Sarvaanga abhyanga (full body massage with medicated oil), Baashpa sweda & Naadi sweda (steam bath), Shashtika shali pinda sweda -SSPS (sudation with a bolus prepared by boiled rice), Nasya, Shirodhara (oil drip over the forehead) and Vasti (oil and decoction enemas), are found to be beneficial in the management of CP. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Present study is focused only on few panchakarma procedures which are commonly used and found effective in the management of CP like Udwartana, Sarvaanga abhyanga, Baashpa sweda & Naadi sweda, Shashtika shali pinda sweda, Nasya and Vasti.…”
Section: Some Effective Panchakarma In Cpmentioning
confidence: 99%
See 1 more Smart Citation
“…In India it is reported that incidence of CP is 3 per 1000 live births 2 . Its pathology lies in developing brain chiefly cerebrum, brain stem, gyri, middle cerebral artery, thalamus, basal ganglia, cerebellum etc.…”
Section: Introductionmentioning
confidence: 99%